Implementation of a 30° Head up Position on Respiratory Distress in an Infant with Bronchopneumonia - Eriska Nur Handayani; Windy Rakhmawati; Ai Mardhiyah (CV. Utami, 2026)
Bronchopneumonia is one of the leading causes of mortality in children under five years old and, if not managed properly, may progress to Acute Respiratory Distress Syndrome or severe hypoxia. Respiratory distress is one of the most common clinical symptoms observed. The head-up 30° position can reduce the work of breathing, facilitate mucus clearance, and prevent secretion accumulation. This study aimed to describe the response of an infant with bronchopneumonia to the head-up 30° intervention based on changes in respiratory distress indicators. This case report involved one infant with bronchopneumonia who received the head-up 30° position for four days. Parameters measured included respiratory rate, oxygen saturation, and chest retraction before and after the intervention. The results showed an improvement in respiratory parameters following the head-up 30° position; on the second day, when oxygen was reduced to 1 L/min, the respiratory rate decreased from 48 breath/min to 38 breath/min, chest retraction decreased, and oxygen saturation increased from 95% to 100%. The head-up 30° position was effective in improving respiratory distress in an infant with bronchopneumonia.